Authoritarian leadership and cyberloafing: A moderated mediation model of emotional exhaustion and power distance orientation - Zhang, Yajun; Wang, Jingjing; Akhtar, Muhammad Naseer; Wang, Yongqi (Frontiers in Psychology, 2022)
Drawing upon the conservation of resource theory (COR), this study proposes a moderated mediation model of authoritarian leadership on subordinates’ cyberloafing. Paired samples of 360 employees working in 103 teams from Chinese companies were collected at 2 points in time. The results show that authoritarian leadership positively affects subordinates’ cyberloafing and this relationship is mediated by emotional exhaustion. Furthermore, power distance orientation negatively moderates the relationship between authoritarian leadership and emotional exhaustion and also negatively moderates the indirect effect of authoritarian leadership on subordinates’ cyberloafing through subordinates’ emotional exhaustion. Our findings expand and enrich the literature on authoritarian leadership and cyberloafing and have significant practical implications for managing employees in this digital era.